2003
DOI: 10.1016/s0306-4522(02)00700-5
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of hippocampal place cell activity to learning and formation of goal-directed navigation in rats

Abstract: Abstract-Although extensive behavioral studies have demonstrated that hippocampal lesions impair navigation toward specific places, the role of hippocampal neuronal activity in the development of efficient navigation during place learning remains unknown. The aim of the present study was to investigate how hippocampal neuronal activity changes as rats learn to navigate efficiently to acquire rewards in an open field. Rats were pre-trained in a random reward task where intracranial self-stimulation rewards were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
52
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 60 publications
(76 reference statements)
8
52
1
Order By: Relevance
“…Previously, Deadwyler et al (1996) made a similar proposal based on an analysis of the activity of small populations of hippocampal cells in rats solving a delayed-matching-to-sample task. Finally, Kobayashi et al (2003) recorded place cells from rats trained to take fixed trajectories to obtain intracranial stimulation rewards at two specific locations in a cylinder. They found that some cells changed their firing patterns as the rat learned the task and displayed excess firing at the two rewarded locations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, Deadwyler et al (1996) made a similar proposal based on an analysis of the activity of small populations of hippocampal cells in rats solving a delayed-matching-to-sample task. Finally, Kobayashi et al (2003) recorded place cells from rats trained to take fixed trajectories to obtain intracranial stimulation rewards at two specific locations in a cylinder. They found that some cells changed their firing patterns as the rat learned the task and displayed excess firing at the two rewarded locations.…”
Section: Discussionmentioning
confidence: 99%
“…For example, firing fields do not tend to occur in higher numbers near goal locations (Lenck-Santini et al, 2001, 2002 and do not seem to undergo systematic changes when the goal is moved (Speakman and O'Keefe, 1990;Trullier et al, 1999;Lenck-Santini et al, 2001). In contrast, there have been several reports that firing fields occur in excess at goal locations (Gothard et al, 1996;Hollup et al, 2001;Hölscher et al, 2003;Kobayashi et al, 2003).…”
Section: Introductionmentioning
confidence: 91%
“…Enhanced Arc mRNA expression could reflect increased firing of neurons that express information retrieved from memory in their goal-directed activity and thus represent memory traces (Wood et al, 2000;Hollup et al, 2001;Fyhn et al, 2002;Nakazawa et al, 2003;Kobayashi et al, 2003). It is thought that HC place cells and head direction cells found in CA1, postsubiculum, anterior dorsal thalamus, and lateral mammillary nuclei are interacting parts of the rodent navigational system (Leutgeb et al, 2000;Calton et al, 2003) that rely on allocentric and idiothetic information processing (Eichenbaum et al, 1990;Whishaw and Maaswinkel, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The mesolimbic and mesocortical pathways, arising mainly from the ventral tegmental area and innervating the mesial parts of the limbic system, including the NAc, AM, HF, and prefrontal cortex, function in incentive motivational processes (1,(7)(8)(9). It has been reported that reward information is processed in the prefrontal cortex, AM, and ventral tegmental area (3,(23)(24)(25)(26)(27)(28), and spatial information is processed in the HF (5,29,30), both of which then converge on NAc neurons (10,11,15,19). The D1R-KO eliminated the prereward excitatory response in the NAc of mice, whereas the response during and after reward was unchanged.…”
Section: Discussionmentioning
confidence: 99%